Audit committee characteristics and timeliness of financial reporting: Social enterprises evidence - Yusri Huzaimi Mat Jusoh; Siti Noor Azmawaty Abd Razak; Wan Nurul Basirah Wan Mohamad Noor; Ataina Hudayati; Abriyani Puspaningsih; Farah Aida Ahmad Nadzri (Contemporary Economics, 2022)
There was vast research on the effectiveness of audit committees as part of the mechanisms in safeguarding shareholders' interest and also ensuring effective financial reporting by companies. However, studies on the efficacy of audit committees as governance tools in a niche area relating to social enterprises namely cooperative societies in Malaysia is still scarce. Hence, this study intends to investigate the association between audit committee attributes namely audit committee expertise and experience, audit committee meeting frequency and audit committee size to the timeliness reporting compliance among Malaysian cooperative societies. Using qualitative research methods, 158 usable questionnaires from 59 cooperative societies were successfully gathered and analysed using SmartPLS 3 Version 3.2.8. The results obtained provided support to the notion that there is a significant positive relationship between the frequency of meetings on the timeliness reporting compliance and a significant positive relationship between audit committee size on the timeliness reporting compliance. However, the notion expecting a significant positive relationship between the expertise of the audit committee on the timeliness reporting compliance proved to be insignificant. Conclusively, the study provides theoretical and practical support to both literature and practitioners on the importance of having optimum audit committee size and high frequency of meeting in ensuring the timeliness compliance of financial reporting of cooperative societies.
Keywords: M4; 330; Audit committees characteristics; cooperative societies; financial reporting; timeliness compliance; social enterprises